Pyrrolic and Dipyrrolic Chlorophyll Degradation Products in Plants and Herbivores. Issue 28 (28th April 2020) - Ritter, Marcel; Oetama, Vincensius S. P.; Schulze, Daniel; Muetzlaff, Katrin; Meents, Anja K.; Seidel, Raphael A.; Görls, Helmar; Westerhausen, Matthias; Boland, Wilhelm; Pohnert, Georg
Abstract: The degradation of chlorophyll, the omnipresent green pigment, has been investigated intensively over the last 30 years resulting in many elucidated tetrapyrrolic degradation products. With a comparison to the degradation of the structurally similar heme, we hereby propose a novel additional chlorophyll degradation mechanism to mono‐ and dipyrrolic products. This is the first proof of the occurrence of a family of mono‐ and dipyrrols in leaves that are previously only known as heme degradation products. This product family is also found in spit and feces of herbivores with specific metabolomic patterns reflecting the origin of the samples. Based on chromatographic and mass spectrometric evidence as well as on mechanistic considerations we also suggest several tentative new degradation products. One of them, dihydro BOX A, was fully confirmed as a novel natural product by synthesis and comparison of its spectroscopic data. Abstract : On its degradation : Evidence for a further pathway of chlorophyll degradation was found in plants and herbivores. Mono‐ and dipyrrolic compounds, known from heme degradation, were detected and quantified in leaves, spit and feces of herbivores. Novel natural products were detected and the structure of one, dihydro BOX A, was proven by synthesis.